Partnerstwo publiczno-prywatne jako forma świadczenia usług publicznych z zakresu oświaty​ - Majchrowicz-Jopek, Elżbieta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The text discusses the context and background for development of public-private partnership in the education sector. This development is based in the concept of New Public Management (New Governance) widespreaded in the policy and practice of governments since 1980 s. The article discuses an example of involvement of non-public actors in providing education: The Private Financial Initiative (PFI). PFI has become the predominant model for building and operating of new schools in the United Kingdom. The British experiences have been employed by other countries as the number and volume of educational investments conducted in the PPP formula is steadily growing. This process has been illustrated by the relevant European Investment Bank data. The text also features the Polish approach to contracting out public education services i.e. when local authorities entrusts the operation of public school to a private entity. This concept corresponds with the idea of community schools where local communities become authentic owners of the school itself and its assets.